Human Resource Management: Career Development - Budhathoki, Dhruba Kumar (Journal of Nepalese Business Studies, 2006)
This paper mainly emphasizes on career development which is gaining much importance in recent times in order to retain skilled, competent and result oriented people in the organization. This paper invites special attention in this area of organizations. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.99-100